Human consciousness and the ‘anthropological turn’: theological perspectives on evolutionary anthropology - Breul, Martin (Technische Universität Dortmund, 2025)
Recent discussions between evolutionary and theological anthropology have intensified, particularly through the work of Michael Tomasello. As a key figure in evolutionary anthropology, Tomasello synthesizes extensive empirical research into an accessible ‘natural history’ of core human abilities. He posits that a unique human trait distinguishing us from our closest relatives is the capacity for “collective intentionality”, a concept he adapts from the philosophy of action. In this article, I show that Tomasello’s insights carry significant implications for philosophical and theological debates. Philosophically, his evolutionary framework invites a new understanding of the mind–brain problem, promoting a non-reductive view of human consciousness which questions the basic metaphysical assumptions of the debate by taking a genealogical perspective. Theologically, his work supports a “practical metaphysics”, suggesting that although morality is autonomous, it can lead to theistic interpretations of human existence. This supports the Kantian idea that religion does not precede morality but that religious views of the world are interpretations of human moral life. At the same time, religion is not just an add-on to morality but an interpretation of a human form of life as such. Both discourses exemplify the importance of a genealogical perspective in philosophy and theology, especially reinforcing the necessity of considering the ‘natural history’ of consciousness, free will or religiosity in anthropology.
Religions; 16(3)
Keywords: Evolutionary anthropology; Theological anthropology; Mind–brain debate; Anthropological turn; Natural history; Human consciousness; Collective intentionality; Michael Tomasello; 200; 230; 100; 300; 150; 320